Analisis Beban kerja Mental dan Fisik pada Petugas Keamanan Kampus Menggunakan Metode NASA-TLX dan CVL Studi Kasus: Universitas Negeri Gorontalo - Ayuni, Dewi Riasty; Lahay, Idham Halid; Uloli, Hendra (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The work done by security officers is to control the work environment, regulate student and lecturer vehicle traffic, escort guests and conduct security patrols around the campus. Security officers use a shift system which of course affects the human circadian rhythm. The amount of work done by security officers within 12 hours causes security officers to experience fatigue and excessive sleepiness. This study aims to analyze the mental and physical workload of security officers. The method used is NASA-TLX to determine the level of mental workload, cardiovascular load to determine the pulse rate. The results of research based on NASA-TLX state that the mental workload experienced by security officers in the morning and night shifts is mostly high. In the physical workload in the morning and night shifts there is no fatigue seen from the CVL percentage of less than 30%.